TESTING OF TECHNOLOGY ACCEPTANCE MODEL ON E-LEARNING BASED EDMODO FRAMEWORK: A PERSPECTIVE OF STUDENTS PERCEPTION - Aang Kisnu Darmawan; Nur Umamah (Universitas Bina Darma, 2019)
E-learning is the application of Information and Multimedia Technology in the field of Education which is currently the main trend in the learning process in the classroom. E-learning is currently designed by integrating the learning process using features in social media so as to facilitate the interaction of teachers and students that are expected to improve the efficiency and effectiveness of classroom learning. However, in practice there are still few teachers, educators and students who can apply e-learning well, because they think that the application of e-learning is difficult to implement in classroom learning. Edmodo is one of the most used e-learning framework because of its ease in its application. This study aims to measure the level of student acceptance of the application of edmodo-based e-learning by using the Technology Acceptance Model (TAM). The method used uses the survey method for 160 upper secondary students. Data analysis was performed using Structural Equation Modeling (SEM) with the help of AMOS 24 software. The results showed that the application of Edmodo-based e-learning had a positive and significant effect on students' motivation and learning outcomes in the classroom.